(untitled) (International Journal of Food and Nutritional Sciences, 2022)
For many years, there has been considerable debate over the technology revolution in every sector of the economy. Since then, a decade of studies at the firm and country level consistently reported that IT industry growth is momentous and constructive. This article develops a general framework on the performance parameters of information technology sector. It facilitates in identifying what researchers know and how well versed are they about the impact of technology and various government initiatives in this regard. IT is not simply a tool for automating existing processes, but more importantly an enabler of organizational and industrial changes that can lead to additional gains of the market. The present study has experienced boom and prosperity of the information technology sector in the Indian economy. The various regulations and policies formulated by the government have facilitated the information technology sector in greater aspects. But the success of initiatives and performance parameters would pivot relentless innovation, improving the IT structure and removing different bottlenecks to sustain IT industry.